Clinically uncomplicated Plasmodium falciparum malaria with high schizontaemia: a case report. - Lwin, K; Ashley, E; Proux, S; Silamut, K; Nosten, F; McGready, R (BioMed Central, 2008)
BACKGROUND: The treatment options for acute Plasmodium falciparum malaria are based on the clinician classifying the patient as uncomplicated or severe according to the clinical and parasitological findings. This process is not always straightforward. CASE PRESENTATION: An adult male presented to a clinic on the western border of Thailand with a physical examination and P. falciparum trophozoite count (1.2% of infected red blood cells, IRBC) from malaria blood smear, consistent with a diagnosis of uncomplicated P. falciparum infection. However, the physician on duty treated the patient for severe malaria based on the reported P. falciparum schizont count, which was very high (0.3% IRBC), noticeably in relation to the trophozoite count and schizont:trophozoite ratio 0.25:1. On intravenous artesunate, the patient deteriorated clinically in the first 24 hours. The trophozoite count increased from 1.2% IRBC at baseline to 20.5% IRBC 18 hours following the start of treatment. By day three, the patient recovered and was discharged on day seven having completed a seven-day treatment with artesunate and mefloquine. CONCLUSION: The malaria blood smear provides only a guide to the overall parasite biomass in the body, due to the ability of P. falciparum to sequester in the microvasculature. In severe malaria, high schizont counts are associated with worse prognosis. In low transmission areas or in non-immune travelers the presence of schizonts in the peripheral circulation is an indication for close patient supervision. In this case, an unusually high schizont count in a clinically uncomplicated patient was indicative of potential deterioration. Prompt treatment with intravenous artesunate is likely to have been responsible for the good clinical outcome in this case.